Blackness blurred: (un)belonging, kinship, and métissage in Marie NDiaye's Ladivine. Issue 1 (2nd January 2023) - Moji, Polo B.
Abstract: This article examines elusive freedom and black (un)belonging in France through the work of Marie NDiaye, a prize-winning playwright and author, whose controversial denunciation of the "monstrosity" of President Nicholas Sarkozy's France in 2009 coincided with her being awarded France's highest literary award. Reading the author's fierce attachment to the conception of her blackness as French rather than francophone I analyze the interracial and intraracial dynamics of black French identities in NDiaye's novel Ladivine (2013) alongside her critically acclaimed play Papa doit manger (2003) and short story "Les sœurs" (2008). The analysis frames (un)belonging as contingent belonging, using Tommie Shelby's articulations of "thin" and "thick" conceptions of blackness to read NDiaye's literary representations in conversation with Pap Ndiaye's sociological study of blackness as a minoritization "condition" in France. I explore the representation of métissage (biracial/mixed-race) identities and the trope of passing (as white) in troubling dominant conceptions of "thin blackness" and being able to read race on the body in Ladivine and "Les sœurs." This is followed by an examination of the representation of "monstrous" intimacies of kinship and ancestry as articulations of "thick blackness" by reading Ladivine in conversation with Papa doit manger. I propose that through the poetics of the "thins and thicks" of blackness NDiaye productively challenges the conflation of blackness with "other" origins.